2011
DOI: 10.1039/c0mb00341g
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics study of diabetic retinopathy using gas chromatography–mass spectrometry: a comparison of stages and subtypes diagnosed by Western and Chinese medicine

Abstract: Diabetic retinopathy (DR) is a serious microvascular syndrome of diabetes, and is one of the most frequent causes of blindness in the world. It has three progressive stages with complex metabolic deregulations in the holistic system of Western medicine. Chinese medicine classifies DR into two different syndrome types; integrating Western and Chinese medicine to treat DR is a validated therapeutic approach in China. In this research, the systemic metabolite change of DR was investigated from the viewpoint of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…2-Hydroxybutyric acid, a derivative of a-ketobutyrate, was previously identified as a marker (14,21) and predictor (44) for diabetes. The ketone body, 3-hydroxybutyric acid, was identified as a marker for impaired glucose tolerance (13) and type 2 diabetes (20,21) and was also identified as a marker for DR in the study by Li et al (26). No significant differences in the levels of 2-hydroxybutyric acid and 3-hydroxybutyric acid were found between DR cases and control subjects with diabetes in both the discovery and validation sets (Supplementary Table 8).…”
Section: Unique Signatures Of Hydroxy Fatty Acids In Drmentioning
confidence: 89%
See 1 more Smart Citation
“…2-Hydroxybutyric acid, a derivative of a-ketobutyrate, was previously identified as a marker (14,21) and predictor (44) for diabetes. The ketone body, 3-hydroxybutyric acid, was identified as a marker for impaired glucose tolerance (13) and type 2 diabetes (20,21) and was also identified as a marker for DR in the study by Li et al (26). No significant differences in the levels of 2-hydroxybutyric acid and 3-hydroxybutyric acid were found between DR cases and control subjects with diabetes in both the discovery and validation sets (Supplementary Table 8).…”
Section: Unique Signatures Of Hydroxy Fatty Acids In Drmentioning
confidence: 89%
“…In contrast, plasma or sera have remained the biofluid of choice in metabonomic studies. With these biological matrices, several research groups have reported metabolite markers of global (25,26) and targeted (27)(28)(29) metabonomic analysis. These studies, however, did not account for confounders and comorbidities, such as medication use and kidney disease.…”
mentioning
confidence: 99%
“…Three metabolomic studies have been reported so far in DR research, suggesting enhanced lactate and glucose metabolism, and overactivity of the arginine-toproline pathway. 62,63 In addition, L-aspartic acid and linoleic acid have been found to distinguish different stages of DR. 64 Further investigations may reveal the use of these signatures as biomarkers or even therapeutic targets. Furthermore, hyperglycemia has been linked to alterations in epigenetic modifications, which is a relatively new field of interest in DR research.…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…In ophthalmology, metabolomics has been used to study various eye diseases including glaucoma [10][11][12][13][14][15][16] , age-related macular degeneration [17][18][19] , diabetic retinopathy [20][21][22] , keratoconus [23] , refractive error [24,25] , retinal detachment [26] , uveitis [27,28] , dry eye [29,30] , and other ocular surface diseases [31] . Analyses have been performed on tear fluid [23,[29][30][31][32] , aqueous humor [24,25,33,34] , vitreous humor [20,26,27,35,36] , cornea [37][38][39] , conjunctiva [40] , and lens [41,42] samples.…”
Section: Metabolomics In Ophthalmologymentioning
confidence: 99%